2011
DOI: 10.1371/journal.pone.0021575
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Cue Integration as a Developmental Outcome of Reward Mediated Learning

Abstract: Average human behavior in cue combination tasks is well predicted by Bayesian inference models. As this capability is acquired over developmental timescales, the question arises, how it is learned. Here we investigated whether reward dependent learning, that is well established at the computational, behavioral, and neuronal levels, could contribute to this development. It is shown that a model free reinforcement learning algorithm can indeed learn to do cue integration, i.e. weight uncertain cues according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 76 publications
1
32
1
Order By: Relevance
“…The simulation setup is based partly on [10]. At each time step, a stimulus is generated randomly in one of the 30 discrete positions and each sensor observes a noisy representation of it.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The simulation setup is based partly on [10]. At each time step, a stimulus is generated randomly in one of the 30 discrete positions and each sensor observes a noisy representation of it.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…For example, artificial neural networks can be trained to perform Bayesian cue integration and causal inference using reinforcement learning [53]. Specifically, the network learns to optimally combine sensory information by predicting the reward that an action will produce for a given set of sensory information.…”
Section: Development and Calibration Of Multisensory Integrationmentioning
confidence: 99%
“…Psychophysical studies have shown that animals and humans can behave as optimal Bayesian observers—they integrate noisy sensory cues, their own predictions and prior beliefs in order to maximize the expected outcome of their actions (Kording and Wolpert, 2004; Ernst, 2007; Navalpakkam et al, 2010; Rao, 2010; Weisswange et al, 2011; Karim et al, 2012). A key to maximizing the outcome is to have knowledge of the certainty of sensory evidence, for higher degrees of uncertainty encourage the nervous system to weaken its belief in the ongoing model and to explore alternative stimulus-outcome associations (Karlsson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%